Sugarcane Yield Response to Furrow-Applied Organic Amendments on Sand Soils - J. Mabry McCray; Shangning Ji; Leslie E. Baucum (International Journal of Agronomy)
Organic amendments have been shown to increase sugarcane yield on sand soils in Florida. These soils have very low water and nutrient-holding capacities because of the low content of organic matter, silt, and clay. Because of high costs associated with broadcast application, this field study was conducted to determine sugarcane yield response to furrow application of two organic amendments on sand soils. One experiment compared broadcast application (226 m3 ha−1) of mill mud and yard waste compost, furrow application (14, 28, and 56 m3 ha−1) of these materials, and no amendment. Another experiment compared furrow applications (28 and 56 m3 ha−1) of mill mud and yard waste compost with no amendment. There were significant yield (t sucrose ha−1) responses to broadcast and furrow-applied mill mud but responses to furrow applications were not consistent across sites. There were no significant yield responses to yard waste compost suggesting that higher rates or repeated applications of this amendment will be required to achieve results comparable to mill mud. Results also suggest that enhancing water and nutrient availability in the entire volume of the root zone with broadcast incorporation of organic amendments is the more effective approach for low organic matter sands.